KOMIK DAN PENDIDIKAN: SEBUAH KAJIAN BUDAYA POPULER - Adi, Agung; L Sigai, Ervantia Restulita (Dharma Duta, 2025)
This article elaborates on the development of comics in Indonesia, with particular attention to their previously marginalized position within the realm of education. Comics have long been dismissed in educational settings, often regarded as mere imaginative works whose image-dominated content was believed to discourage students from reading. In contrast to this view, comic scholars advocate a more serious appreciation of comics. Elements such as narrative structure, characterization, and the messages conveyed by comic authors constitute significant strengths that are comparable to those found in other esteemed forms of literature. This recognition has increasingly gained traction among contemporary educators. Consequently, comics—once prohibited in educational contexts—have now emerged as valuable learning resources across various levels of education in Indonesia